1997
DOI: 10.1111/j.1834-7819.1997.tb00129.x
|View full text |Cite
|
Sign up to set email alerts
|

The current status of low level laser therapy in dentistry, Part 1. Soft tissue applications

Abstract: Despite more than 30 years of experience with low level laser therapy (LLLT) or 'biostimulation' in dentistry, concerns remain as to its effectiveness as a treatment modality. Controlled clinical studies have demonstrated that while LLLT is effective for some specific applications, it is not a panacea. This paper provides an outline of the biological basis of LLLT and summarizes the findings of controlled clinical studies of the use of LLLT for specific soft tissue applications in dentistry. Areas of controver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
177
2
30

Year Published

2002
2002
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 267 publications
(222 citation statements)
references
References 43 publications
4
177
2
30
Order By: Relevance
“…These are generally variants of either gallium:aluminium:arsenide which emit in the near infrared spectrum (700-940 nm). 25 In our study we used gallium:aluminium:arsenide laser for 20 seconds, 980 nm wavelength, 15 J/cm 2 . The results of this study showed that the mean pain intensity in VAS1 in the group receiving laser was lower than in the group that did not receive laser (P = 0.031).…”
Section: Discussionmentioning
confidence: 99%
“…These are generally variants of either gallium:aluminium:arsenide which emit in the near infrared spectrum (700-940 nm). 25 In our study we used gallium:aluminium:arsenide laser for 20 seconds, 980 nm wavelength, 15 J/cm 2 . The results of this study showed that the mean pain intensity in VAS1 in the group receiving laser was lower than in the group that did not receive laser (P = 0.031).…”
Section: Discussionmentioning
confidence: 99%
“…At low doses (2 J/cm 2 ) phototherapy stimulates fibroblast proliferation while higher doses (16 J/cm 2 ) are suppressive, pointing to the dose dependence of biological responses after light exposure. Low energy laser irradiation alters the cellular function by influencing protein synthesis, cell growth and differentiation, cell motility, membrane potential and binding affinities, neurotransmitter release, ATP synthesis, and prostaglandin synthesis [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…20,29 Angiogenesis is also beneficial to OTM by allowing greater movement of oxygen, nutrients and chemical mediators of inflammation, and by facilitating the infiltration of repair cells. 30 It also promotes the arrival of osteoclasts, cells that arise from monocytes in the bone marrow and are transported through the bloodstream.…”
Section: Discussionmentioning
confidence: 99%